"Crawling Out of the Cocoon": Patients' Experiences of a Physical Therapy Exercise Intervention in the Treatment of Major Depression. Issue 8 (1st August 2016) - Danielsson, Louise; Kihlbom, Birgitta; Rosberg, Susanne
Abstract: Background: Although the effectiveness of physical exercise for depression has been studied for many years, few studies have described patients' experiences of what exercise means to them, beyond the biological focus. Moreover, exercise as a treatment for depression is rarely explored in a physical therapy context. Objectives: The purpose of this study was to explore a physical therapy exercise intervention, as experienced by people with major depression. Design: This study had an inductive approach and used qualitative content analysis. Methods: Semistructured interviews were conducted with 13 people who participated in physical therapist–guided aerobic exercise in a randomized controlled trial. All participants were diagnosed with major depression according to the Diagnostic and Statistical Manual of Mental Disorders . Data were collected and analyzed in an inductive manner using qualitative content analysis according to Graneheim and Lundman. Results: Four categories emerged: (1) struggling toward a healthy self, (2) challenging the resistance, (3) feeling alive but not euphoric, and (4) needing someone to be there for you. The participants experienced that although the exercise intervention was hard work, it enhanced the feeling of being alive and made them feel that they were doing something good for themselves. These feelings were a welcome contrast to the numbness and stagnation they experienced during depression. Limitations: The study was conducted in Swedish primary care. Transferability of results must be viewed in relation to context. Conclusions: Exercise in a physical therapy context can improve the patients' perception of their physical ability and create a sense of liveliness, improving their depressed state. The therapeutic relationship is essential for supporting the patient's vulnerability and ambiguity in an empathic and perceptive way.